potensi ekstrak alga merah jenis Eucheuma cottoni sebagai antibakteri - faridah, susanti; Nuryanti, Siska; Rusli, Rusli (PHARMACY UMI JOURNAL SYSTEM, 2024)
One type of algae cultivated in Indonesia is the red algae Eucheuma cottoni. Red algae are able to produce active metabolite ingredients to protect themselves from attacks by disease and predators. Initially, algae was only used for vegetables and it was not known what substances were contained in algae. As time goes by, knowledge about algae continues to grow. The red algae Eucheuma cottoni contains the chemical carrageenan, a polysaccharide compound produced from various types of red algae that has antimicrobial, anti-inflammatory, antipyretic, anticoagulant and other biological activities. This research aims to determine the potential of red algae extract as an antibacterial. This research uses a literature study approach where references are obtained through 4 data bases, namely Google Scholar, PubMed, Science Direct and Garuda, then based on the search, 8 journals are obtained that meet the inclusion and exclusion criteria. Based on the results of literature studies, it was found that red algae extract has antibacterial activity against the bacteria Salmonella thypi, Staphylococcus aureus, Staphylococcus epidermidis, Bacilus subtilis, and Escherichia coli. Key words: (Antibacterial, Eucheuma cottoni, Red Algae).